CREATION OF OPTIMUM CONDITIONS FOR PROPAGATION OF SACCHAROMYCES CEREVISIAE YEAST - Nabiyeva F.S.; Fayzullayeva Kh. B.; Karakulov A.G. (Journal of new century innovations, 2023)
Annotation. Saccharomyces cerevisiae is of great importance as a biotechnological object, various sources of nutrients are currently used to grow yeast cultures. It is known that crop waste can be recycled or used for various purposes. In the article, molasses is used for the industrial production of Saccharomyces cerevisiae.